"The Chicken or the Egg": Barriers and Facilitators to Collaborative Care for People With Comorbidity in a Metropolitan Region of South Australia. (2nd January 2017) - Groenkjaer, Mette; de Crespigny, Charlotte; Liu, Dennis; Moss, John; Cairney, Imelda; Lee, Deb; Procter, Nicholas; Galletly, Cherrie
Abstract : Mental health disorder and alcohol and other drug comorbidity is prevalent in Australia. This qualitative study used semistructured interviews ( N = 20) to elicit clinicians' and workers' knowledge, experiences, and opinions regarding issues pertaining to service needs of people with comorbidity in a metropolitan region of South Australia. The study revealed barriers to effective access and delivery of comorbidity care by MH and AOD services. Participants reported difficulties with identification, access, suitability, policy, funding, and collaboration between sectors and services responding to comorbidity. Results suggest that these models of practice were inadequate influencing the delivery, consistency, and reliability of comorbidity care.